2007
DOI: 10.1109/tbme.2006.888836
|View full text |Cite
|
Sign up to set email alerts
|

Study of On-Line Adaptive Discriminant Analysis for EEG-Based Brain Computer Interfaces

Abstract: A study of different on-line adaptive classifiers, using various feature types is presented. Motor imagery brain computer interface (BCI) experiments were carried out with 18 naive able-bodied subjects. Experiments were done with three two-class, cue-based, electroencephalogram (EEG)-based systems. Two continuously adaptive classifiers were tested: adaptive quadratic and linear discriminant analysis. Three feature types were analyzed, adaptive autoregressive parameters, logarithmic band power estimates and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 23 publications
3
93
0
Order By: Relevance
“…Reinforcement learning would require a stable physiological response to a stimulating input. Vidaurre et al found a direct correlation between the personally perceived stress level and SCL in nondisabled subjects performing a VR task while sitting on a chair [45]. In such a case, the SCL could be exploited by a reinforcement learning algorithm for classification and subsequent control of stress.…”
Section: Real-time Capability Of Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforcement learning would require a stable physiological response to a stimulating input. Vidaurre et al found a direct correlation between the personally perceived stress level and SCL in nondisabled subjects performing a VR task while sitting on a chair [45]. In such a case, the SCL could be exploited by a reinforcement learning algorithm for classification and subsequent control of stress.…”
Section: Real-time Capability Of Approachmentioning
confidence: 99%
“…An idea proposed by Vidaurre et al suggests use of a classifier in combination with a Kalman filter to train the classifier at run time [45]. The classifier, such as a neural network, could be trained on data from previous experiments and a Kalman filter would adapt the classifier parameters to the patient.…”
Section: Usability In Clinical Settingmentioning
confidence: 99%
“…They require an a priori choice of the structure and order of the signal generation mechanism model. (Anderson & Sijercic, 1996;Schlogl et al, 1997;Anderson et al, 1998;Roberts & Penny, 2000;Burke et al, 2005;Vidaurre et al, 2007). AR methods assume that a signal X(t), measured at time t, can be modeled as a weighted sum of the values of this signal at previous time steps, to which we can add a noise term E t (generally a Gaussian white noise):…”
Section: Parametric Modellingmentioning
confidence: 99%
“…Although helpful, the requirement of such a priori information actually represents a major pitfall for practical BCI applications since the user should decide when and where to direct his/her intentions. In other words, no information of external targets is available to the decoding algorithm (Blankertz et al, 2006;Vidaurre et al, 2007). The complexity of using two adaptive controllers (the user's brain and the decoding algorithm) is not new and has been already raised (McFarland et al, 2006;Vaughan et al, 1996); however, it continues to be an issue, and no satisfying solutions of this problem have been provided (McFarland et al, 2006).…”
Section: Neuroprosthetic Applications: Towards a Smart Brain Computermentioning
confidence: 99%